ETHNIC IDENTITY DEVELOPMENT AS A DETERMINING FACTOR OF ADOLESCENT SOCIALIZATION IN MULTIETHNIC COMMUNITIES: EDUCATIONAL, PSYCHOLOGICAL, AND SOCIO-CULTURAL PERSPECTIVES - Davlatova Saodat Tilovberdiyevna (International Journal of Literature and Language Studies, 2026)
The rapid growth of globalization, migration, and intercultural interaction has transformed multiethnic societies into dynamic environments where adolescents encounter diverse cultural identities and social values. In such contexts, the development of ethnic identity represents a fundamental psychological and socio-cultural process that significantly influences adolescent socialization, interpersonal relationships, civic engagement, and emotional well-being. This study explores the role of ethnic identity development as a determinant of successful adolescent socialization in polyethnic regions, emphasizing its contribution to social adaptation, intercultural competence, and peaceful coexistence. The research employs qualitative content analysis supported by comparative and socio-pedagogical approaches to examine contemporary theories of ethnic identity and their application within multicultural educational settings. The study integrates findings from psychology, sociology, education, and cultural studies to evaluate how family, schools, community organizations, peer groups, and digital communication collectively shape adolescents' ethnic self-awareness and social behavior. The findings indicate that adolescents possessing a well-developed and positive ethnic identity demonstrate higher levels of self-esteem, social responsibility, intercultural tolerance, and civic participation. Conversely, weak or conflicted ethnic identity may contribute to social isolation, discrimination, identity confusion, and intergroup conflicts. Educational institutions play a critical role by implementing multicultural curricula, inclusive teaching strategies, intercultural dialogue programs, and value-based education that promote mutual respect and appreciation of cultural diversity.